2017
DOI: 10.1097/md.0000000000006865
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance and prognostic value of Triosephosphate isomerase expression in gastric cancer

Abstract: Triosephosphate isomerase (TPI) is highly expressed in many human cancers and is involved in migration and invasion of cancer cells. However, TPI clinicopathological significance and prognostic value in gastric cancer (GC) are not yet well defined. The aim of the present work was to evaluate TPI expression in GC tissue and its prognostic value in GC patients.TPI expression was analyzed in 92 primary GC tissues and 80 adjacent normal mucosa tissues from GC patients undergoing gastrectomy by immunohistochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…Our western blot result indicated that the TPI protein is significantly upregulated in the tumor samples relative to the adjacent normal tissue. Similar to our observation, the overexpression of the TPI has been reported in various human tumors (Altenberg & Greulich, ) and importantly linked to the progression, migration, and invasion of the tumor cells (T. Chen et al, ). Furthermore, our data established that the post‐transcriptional regulation seems to be the likely mechanism for the upregulation of the TPI protein.…”
Section: Discussionsupporting
confidence: 92%
“…Our western blot result indicated that the TPI protein is significantly upregulated in the tumor samples relative to the adjacent normal tissue. Similar to our observation, the overexpression of the TPI has been reported in various human tumors (Altenberg & Greulich, ) and importantly linked to the progression, migration, and invasion of the tumor cells (T. Chen et al, ). Furthermore, our data established that the post‐transcriptional regulation seems to be the likely mechanism for the upregulation of the TPI protein.…”
Section: Discussionsupporting
confidence: 92%
“…Proteomic analysis of sera from pancreatic cancer patients showed TPI1 as one of the most abundant proteins in patients with poor survival before and after chemotherapy and could be further investigated as a prognostic marker as its levels gradually increase as the disease progresses [123]. The prognostic value TPI1 was also evaluated in gastric cancer, where patients with higher TPI1 expression had lower overall survival [124].…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent years, the molecular mechanisms of the relationship between TPI and cancer progression have been started to be investigated. The results of the studies provide strong evidence that TPI enzyme may be involved in tumor progression, drug resistance, invasion and metastasis …”
Section: The Role Of Triosephosphate Isomerase In Cancermentioning
confidence: 92%
“…In one of the recent studies, TPI has been defined as a potential tumor marker in gastric cancer . Chen et al .…”
Section: The Role Of Triosephosphate Isomerase In Cancermentioning
confidence: 99%
See 1 more Smart Citation